Merging Biosecurity, Vaccination plans and Risk Identification and Management: A Necessity in Risk Communication? - Noordhuizen, Jos P. (Contemporary Research and Perspectives in Biological Science Vol. 11, 2025)
Professional communication is not widely used in veterinary practice. The potential role and power of risk identification and risk management in disease control are largely underestimated in dairy veterinary practice. This paper addresses key domains of veterinary preventive medicine including the integration of vaccination plans within herd health and productivity programs, and implementing risk identification and risk management plans, and ultimately emergency risk communication in situations of population medicine in animal and human populations. Vaccination plans are mostly integrated into herd health and productivity programs, but could be integrated into an overall biosecurity strategy (animals and humans). Both domains should be operational jointly on food animal production farms because they appear to be economically beneficial. The potential risk of economic losses due to diseases is drastically lowered. A dairy farm is used for illustration purposes. Professional communication plays a paramount role in increasing the compliance of the farmer to vaccination plans and biosecurity, as part of an extended herd health and productivity program. Professional communication is not comparable to emergency risk communication, such as should be implemented in outbreaks of highly contagious, notifiable diseases on both farms and in humans, the latter, such as in the case of a Covid-like epidemic. This paper highlights that there is enormous room for improvement in emergency risk communication in a COVID-19-like situation. Public health authorities should be much better prepared for this, including a sound formation of officials in the domain of emergency risk communication.